Inflation and growth: Explaining a negative effect - Gillman, M.; Harris, Mark; Mátyás, L. (2004)
The paper presents a monetary model of endogenous growth and specifies an econometric model consistent with it. The economic model suggests a negative inflation-growth effect, and one that is stronger at lower levels of inflation. Empirical evaluation of the model is based on a large panel of OECD and APEC member countries over the years 1961-1997. The hypothesized negative inflation effect is found comprehensively for the OECD countries to be significant and, as in the theory, to increase marginally as the inflation rate falls. For APEC countries, the results from using instrumental variables also show significant evidence of a similar behavior. The nature of the inflation-growth profile and differences in this between the regions are interpreted with the credit production technology of the model in a way not possible with a standard cash-only economy.